Improvement Reproductivity of Jalak Bali (Leucopsar rothschildi Stresseman) Balinese Rare Animal ( Through the Method DNA Sexing and Improvement of Feed Quality) - Hariadi, Mas’ud; Utomo, Budi; Hermadi, Herry Agoes (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Jalak Bali population or Curik bali (Leucopsar rothschildi Stresseman) in nature is estimated to never exceed several hundred tails. In the 1960s hundreds of Bali Starlings were sent to the United States and Singapore. Then also to Europe. In the United States and Europe this breed is growing rapidly in a number of zoos. But in western Bali, the population is rapidly decrease to invite world attention and concern. The year 1966 has led the Bali Starling into an endangered species group in IUCN's Red Data Book as a type whose condition is classified as "critical" (Prana et al., 2006) Breeding Jalak Bali at Surabaya Zoo (KBS) is currently quite encouraging but there has been no touch of technology yet from university researchers in Indonesia. Trying systems try from the KBS keeper should be given the basis of science and technology cultivation is more intensive. For example how to determine sex (sexing) is still traditional, namely by determining the differences contained in the parts - body parts, sounds and techniques "pendulum". Besides, the guarantee of the authenticity of captive breeding is also doubtful. Similarly, the feeding is still natural, as well as insect eggs (kroto), caterpillars, crickets and voer with a 22% protein content that is prone to contamination with disease agents or other toxic materials. Similarl hygine of these feed ingredients is difficult to control. The proposed study consists of two stages, each stage lasting for one year. The first stage (first year) includes the authenticity / purity test of Jalak Bali Jalak food and the way of sexing with DNA analysis methods. To test the authenticity / purity of DNA analysis performed from blood samples or feathers Jalak Bali from several breeding locations and existing in nature. Sexing is done in a traditional way compared to DNA analysis (PCR). The second stage of research (second year) is the improvement of Bali Starling reproduction with improved quality of feed from combination of natural ingredients with the addition of protein supplements such as lysine, methionine and vitamins processed in the form of granules or pellets can act as feed flushing. Can improve the reproductivity and productivity of Jalak Bali.